Design and implementation of embedded auto car parking system using FPGA for emergency conditions - Khor Jing Yong; Muataz H. Salih (Institute of Advanced Engineering and Science, 2019)
An automatic car parking system using FPGA based on emergency conditions was proposed to detect the driver’s condition and perform specific tasks such as warn the drivers and automatic parking depends on the behavior of the driver. Long journey driving on highway will lead loss of concentration of driver quickly and also cause the driver doze off. Based on statistics, driver tends to fall asleep more on high-speed, long, boring highway. Most crashes occur between 4.00a.m-6.00a.m and midnight 12.00a.m till 2.00a.m. Besides, heart attack during driving will also harm to other road users. The risk of accident will increase due to these conditions. In this paper, automatic car parking system using FPGA based on emergency conditions was proposed to detect the driver’s condition and perform specific tasks such as warn the drivers and automatic parking depends on the behavior of the driver. At the same times, this system can avoid all the obstacles and cars on the road from time to time. Input data management unit was designed as control unit for input data sensors of input and output control. Main processing was designed as speed controller and also the steering controller. Speed controller used to control the speed of vehicle while driving on the road by detecting the obstacles. Steering controller was designed to control automatic car parking and also assisted with sensors around the vehicles. Sensors were tested with many materials so that the system can flexible with any conditions. The total of 1083 logic elements and 676 registers being used in this project and up to 1.6GHz as operating frequency. The complete design is able to avoid obstacles surrounding of host vehicles and parked at a safe area automatically after heart attack of driver detected. Then, GSM send GPS coordination to hospital.